Studi kasus pemanfaatan schedule dan predictive maintenance untuk menentukan standard lifetime engine excavator Komatsu PC2000-8 - Gunawan, Budi S.; Finahari, Nurida; Farid, Akhmad (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
PT. Saptaindra Sejati has a standard lifetime engine which aims to maintain the reliability of the excavator engine when operated. The company is trying to change these standards so that the operational period of the machine is longer by changing the maintenance schedule strategy and utilizing predictive maintenance as a tool for monitoring changes in engine performance conditions. This research is a case study that examines changes in treatment strategies. Tests were carried out using 2 PC2000-8 excavator units as a comparison, by carrying out different maintenance schedules. The difference in treatment is in the form of a schedule for changing the engine oil and oil filter at intervals of 500 HM (Hour Meter, operational period) and 250 HM. The different treatments were carried out after the 18000 HM usage period was reached, which is the standard engine usage period. Monitoring is carried out on oil quality and the level of wear particles contained in the oil. The results of the case study show that the 2 units have different lifetimes, where the unit with a maintenance schedule of 250 HM post 18000 HM has a longer lifetime. A faster oil and engine oil filter change schedule has been proven to reduce wear of parts in the engine. This finding is useful for maintaining engine performance even though it has passed the previously determined lifetime standard so that unit productivity becomes longer and a new standard can be determined for engine lifetime with a different maintenance schedule.